FINANCIAL RISKS OF REGIONAL BUDGET FORMATION (Ustozlar uchun, 2024)
Abstract: This article examines the financial risks associated with the formation of regional budgets, focusing on the challenges and strategies for risk mitigation. Regional budgets play a crucial role in the economic development of a country, as they allocate resources for vital public services and infrastructure projects. However, the process of budget formation is fraught with various risks, including economic fluctuations, revenue uncertainties, and expenditure pressures. The article discusses the key sources of financial risks in regional budget formation and analyzes their impact on budget sustainability. It also explores the role of financial planning, risk assessment, and monitoring mechanisms in managing these risks. The findings suggest that effective risk management strategies, such as diversification of revenue sources, prudent fiscal policies, and transparent budgeting practices, are essential for ensuring the stability and sustainability of regional budgets. The article concludes with recommendations for policymakers and budget planners to enhance the resilience of regional budget systems against financial risks.